If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying h = 2(-3) + 4 Multiply 2 * -3 h = -6 + 4 Combine like terms: -6 + 4 = -2 h = -2 Solving h = -2 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Simplifying h = -2
| M+8+14=31 | | 8u-16=-3(u+9) | | -4w-9=2(5x+9) | | g3=1/8 | | 63-x=35-8x | | 8b-2b-4=6 | | 7x-11-3x=3x+19 | | 44x+2(5x-6)=-3x-39 | | (5x-2)5= | | 24n-10n+36= | | 10z-z=3+3z-3-12 | | 47g^2+50g=0 | | 7[x+(-11)]+(-3)=-53 | | X*11=35 | | 6x-108/5=2x | | -31+8x=29+6x | | y=29-4(6) | | 4sin^2x+2=5 | | y=29-4(5) | | X(3x+2)=23 | | y=29-4(4) | | 4/5=x-3/9 | | 7[x+(11)]+(-3)=-53 | | 2/5(d-3)=30 | | y=29-4(1) | | 6x-30=x-25 | | 9g-15=21 | | 3.4x=1.8x+2.5 | | 5x-6+2x=9x-7 | | 9j^2+42j+49=0 | | 3x^2+15x-9.1=0 | | h=3(1)+1 |